2007
DOI: 10.1177/0022002706298135
|View full text |Cite
|
Sign up to set email alerts
|

What Leads Some Ordinary Arab Men and Women to Approve of Terrorist Acts Against the United States?

Abstract: Findings from representative national surveys in Algeria and Jordan show that neither religious orientations, judgments about Western culture, nor economic circumstances account for variance in approval of terrorist acts against U.S. targets. Alternatively, in both countries, approval of terrorism against the United States is disproportionately likely among men and women with negative judgments about their own government and about U.S. foreign policy. Taken together, these findings suggest that approval of ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(121 citation statements)
references
References 31 publications
5
114
2
Order By: Relevance
“…The analysis of the data presented here can thus allow us to draw conclusions about the possible overlap in the attitudinal and socio-economic profiles of those who sympathize with these two 'theologies'. The corresponding choice of dependent variables follows previous examinations of the political and social dimensions of public support for Islamist ideas (Tessler/Robbins 2007;Jamal 2006). …”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the data presented here can thus allow us to draw conclusions about the possible overlap in the attitudinal and socio-economic profiles of those who sympathize with these two 'theologies'. The corresponding choice of dependent variables follows previous examinations of the political and social dimensions of public support for Islamist ideas (Tessler/Robbins 2007;Jamal 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Previous quantitative explorations by Tessler & Robbins (2007) as well as Mostafa & al-Hamdi (2007) showed that negative views of US foreign policies correlated with greater support for political violence against the United States. The following analysis will thus test Hypothesis I: Among Muslim publics, support for political violence against US civilians is associated with negative views of US foreign policies toward the Middle East.…”
Section: Theory and Hypothesesmentioning
confidence: 96%
“…Arab and Muslim countries failed to detect any direct relation between religious practice or identity and the support for violence, international conflict or groups such as the Taliban and al Qaeda (Fair, Malhotra & Shapiro, 2012;Mousseau, 2011;Shapiro & Fair, 2009;Tessler & Robbins, 2007). On the other hand, Blaydes & Linzer (2012) found religiosity to be positively related to Anti-Americanism as measured in negative views of US culture.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…4 The first two correspond to Hypotheses 1 and 2 in [62]. 5 Advocates of this view often reference "the verse of the sword" in the Quran (Sura 9:5) to justify the link between religious practice and militancy: "Then, when the sacred months have passed, slay the idolaters wherever ye find them, and take them captive, and besiege them, and prepare for them each ambush.…”
Section: Piety and Religious Practicementioning
confidence: 99%
“…Similarly, research on Palestinian public opinion towards Israel has repeatedly found that the perception of Israel as posing a threat is strongly associated with support for violence, but that support for political Islam exhibits no association [80][81][82]. National surveys of Algeria and Jordan in 2002 also showed that while higher levels of religious involvement did not make individuals more likely to approve of terrorist acts against the US, there was a significant relationship between respondents' attitudes towards their government and US foreign policy and their support for terrorism [62].…”
Section: Islamist Politicsmentioning
confidence: 99%